The Effectiveness of Wogonin on Treating Cough Mice With Mycoplasma Pneumoniae Infection - Liang, Mingchuan; Meng, Yanli; Wang, Xiaoxi; Wang, Lei; Tang, Guixin; Wang, Weiming (Frontiers in Molecular Biosciences, 2022)
Background: Cough is the main symptom of mycoplasma pneumoniae (MP) infection. Cough potential protein transient receptor potential A1 (TRPA1) plays an important role in cough reflex. The purpose of this study was to clarify the mechanism of wogonin, the effective component of Qinbai Qingfei Concentrated Pill (Qinbai), in the treatment of cough after MP infection. Methods: Biacore™ system was used to detect whether there was specific binding between Qinbai and cough potential protein TRPA1. Biacore™ fishing technology and UPLC-Q-TOF-MS technology were used during fishing combined active components and identification and analysis of recovered samples. The expression levels of TRPA1, Substance P (SP) and Calcitonin Gene-Related Peptide (CGRP) cough-related proteins and mRNA in the lung tissues from each group were detected by immunohistochemistry, western blot and real-time PCR. Results: Biacore™ results showed that Qinbai had strong specific binding to TRPA1 protein with a binding value of 99.0 resonance unit (RU). The samples obtained from angling were identified and analyzed by UPLC-Q-TOF-MS as wogonin. The results of immunohistochemistry, western blot and real-time PCR showed that compared with the model group, the wogonin group had lower expressions of mRNA, TRPA1, SP and CGRP in the lung tissue of cough mice with MP infection (p < 0.01 or p < 0.05), and the effects were superior to those of azithromycin and pentoxyverine control groups. Conclusion: Wogonin can treat cough after MP infection by affecting the expressions of cough-related proteins, such as TRPA1, SP, and CGRP. This study provided a theoretical foundation for the clinical research of Qinbai.